Ensuring the Security of the Educational Environment: Cases of US, Russia and Europe - V. V. Kabernik; O. A. Timofeyeva (Vestnik MGIMO-Universiteta)
The article deals with security, including informational, educational environment. The article considers experience of the United States and Europe, including specific examples. Given a classification of the major threats and they are allocated on the basis of foreign and domestic experience. The article also determines the range of problems actually facing educational institutions and regularly described in special reports on the subject. Provides an overview of a set of measures designed to regulate access to inappropriate content, with special attention given to the phenomenon of social networks that put new challenges in ensuring security of the educational environment.